2014
DOI: 10.1002/cncr.28617
|View full text |Cite
|
Sign up to set email alerts
|

Lack of reduction in racial disparities in cancer‐specific mortality over a 20‐year period

Abstract: BACKGROUND:To the authors' knowledge, it remains unknown whether race-based differences in cancer outcomes have changed with time. In the current study, the authors assessed whether racial disparities in cancer-specific mortality have improved over the last 20 years. METHODS: The Surveillance, Epidemiology, and End Results program was used to identify 2,713,474 patients diagnosed between 1988 and 2007 with either lung, breast, prostate, or colorectal cancer (the leading 3 causes of cancer-related mortality amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
193
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 223 publications
(210 citation statements)
references
References 21 publications
15
193
2
Order By: Relevance
“…We did not find that the number of dissected LNs had an impact on outcome, consistent with prior work [26,27], although some have found an association between the number of examined LNs and outcomes in select situations [28,29]. We did not find a relationship between Black race and increased PCSM, in contrast to some prior research [30], although others have found that racial disparities in outcomes might be partially explained by adjustment for stage at diagnosis, treatment received, and other clinical and demographic factors, including access to care [31,32].…”
Section: Discussionsupporting
confidence: 83%
“…We did not find that the number of dissected LNs had an impact on outcome, consistent with prior work [26,27], although some have found an association between the number of examined LNs and outcomes in select situations [28,29]. We did not find a relationship between Black race and increased PCSM, in contrast to some prior research [30], although others have found that racial disparities in outcomes might be partially explained by adjustment for stage at diagnosis, treatment received, and other clinical and demographic factors, including access to care [31,32].…”
Section: Discussionsupporting
confidence: 83%
“…In fact a recent study comprising the SEER data in the US showed that there has been no reduction in disparity in prostate cancer mortality in African-American men over the past 20 years. 31 This means that more needs to be done to identify and narrow the gap in current management of prostate cancer in African-Caribbean men in order to achieve discernible results.…”
Section: Management and Outcomesmentioning
confidence: 99%
“…In women, the rate varies only slightly among countries with a very high HDI (85 per 100.000) versus countries with a low HDI (87 per 100.000). These data should be interpreted with caution since the interpretation of the differences in the incidence of cancer based on HDI values may reflect differences in the quality of the information [11][12][13].…”
Section: Introduction and Overall Cancer Burdenmentioning
confidence: 96%